Literature Review: Anxiety in Pregnant Women during the Covid-19 Pandemic - Nadila Imania Awanda; Dwi Handayani (Universitas Ahmad Dahlan, 2023)
Background: The prevalence of pregnant women during the Covid-19 pandemic increased by 72% compared to before the pandemic. The increase in the number of pregnant women during the Covid-19 pandemic goes hand in hand with the increase in the prevalence of pregnancy-related anxiety which can be influenced by internal and external factors and which, in turn, may impact the health of the mother and her baby. The purpose of this literature review is to examine pregnancy-related anxiety during the Covid-19 pandemic. Method: The research is literature review research. The data sources used were Google Scholar and PubMed databases from 2019-2021. The keywords used were “anxiety in pregnant women during a pandemic” (in English) and “kecemasan ibu hamil di masa pandemi” (in Indonesia). Twenty-one articles with the most relevant topics were analyzed comprehensively. Results: Pregnant women aged <20 and >35 years old who only get a primary and secondary education, have a lack of knowledge, are working, have lower economic status, and do not receive support from their husbands are at risk of experiencing anxiety during the Covid-19 pandemic. The anxiety level of pregnant women during the Covid-19 pandemic increased compared to before the pandemic. Conclusion: There is a relationship between age, education, knowledge, employment status, economic status, husband's support, and anxiety in pregnant women during the Covid-19 pandemic. There is a difference in the anxiety level of pregnant women before and during the Covid-19 pandemic. Pregnant women are expected to be able to prepare for and manage their pregnancy during the Covid-19 pandemic and the husband’s support is an important element during pregnancy, especially during a pandemic.